Case report: Psychosis with catatonia in an adult man: a presentation of neurosarcoidosis - Van Hoye, Griet; Willekens, Barbara; Vanden Bossche, Stephanie; Morrens, Manuel; Van Den Eede, Filip (Frontiers in Psychiatry, 2024)
1 Abstract Introduction: Sarcoidosis is a multisystem non-caseous granulomatous disease of unknown origin with predominant lung involvement and a variable clinical course. Although rare, neuropsychiatric manifestations such as confusion, problems in orientation, memory dysfunction, delusions, hallucinations and catatonia can be presenting features of sarcoidosis with nervous system involvement, also known as neurosarcoidosis. Case description: We present a 39-year-old man with acute-onset vertigo, balance problems and confusion quickly developing delusions, hallucinations, catatonic symptoms and suicidal behaviour. Symptoms appeared to be a manifestation of neurosarcoidosis. Diagnostic assessment: The differential diagnosis of psychosis is broad and should include pertinent auto-immune disorders, paraneoplastic, oncologic, metabolic, and neurodegenerative disorders. Basic systemic screening should include blood and urinary tests, a chest X-ray, brain CT scan and ECG. If neurosarcoidosis is suspected, an MRI of the brain with contrast and lumbar puncture are most appropriate. Multidisciplinary collaboration is essential to arrive at a correct diagnosis and effective management of the patient. Discussion: Despite the large number of sarcoidosis and psychosis studies, the etiology and pathogenesis of both illnesses remain incompletely understood. A common inflammatory etiopathological pathway has been postulated. Conclusion: Clinicians should consider organic causes when confronted with a middle-aged patient experiencing a first psychotic episode with an atypical onset, catatonic features, or dysfunction in orientation and/or memory, a complete lack of a positive familial psychiatric history and/or an atypical response to (psycho)pharmacological treatment.